2003
DOI: 10.1103/physrevlett.91.247401
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance in Molecular H Aggregates

Abstract: Direct evidence of superradiance from an organic semiconductor (quaterthiophene) whose molecules are arranged in a H aggregate fashion, is reported. Time resolved photoluminescence measurements show a linear correlation between the radiative lifetime (tau(rad)) of the purely electronic exciton recombination and the inverse of the number (N(C)) of the coherently emitting dipoles, i.e., tau(rad) proportional, variant 1/N(C). These data support the recently developed theoretical models describing the optical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
89
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 25 publications
6
89
0
2
Order By: Relevance
“…In this case, fluorescence emission is observed in resonance to the lowest energy exciton state. The extended exciton states give rise to many peculiar linear and nonlinear optical properties, such as resonant fluorescence [1,2], super radiant emission [7][8][9], high nonlinear susceptibilities [10], efficient exciton-exciton annihilation [11], and energy migration [12][13][14][15]. The latter was already observed by Scheibe et al [16].…”
Section: Introductionmentioning
confidence: 48%
“…In this case, fluorescence emission is observed in resonance to the lowest energy exciton state. The extended exciton states give rise to many peculiar linear and nonlinear optical properties, such as resonant fluorescence [1,2], super radiant emission [7][8][9], high nonlinear susceptibilities [10], efficient exciton-exciton annihilation [11], and energy migration [12][13][14][15]. The latter was already observed by Scheibe et al [16].…”
Section: Introductionmentioning
confidence: 48%
“…8. In an organic quaterthiophene semiconductor whose molecules are arranged in H-aggregate fashion, time-resolved photoluminescence measurements showed that the radiative lifetime had a linear correlation with the inverse of the number of the coherently emitting dipoles, i.e., τ rad ∝ 1/N [102]. More recently, phosphorescence SR was demonstrated in heavy-metal-containing π-conjugated polymers, as a result of the significant spinorbit interaction provided by the large atomic number elements [100].…”
Section: B Molecular Aggregates and Crystalsmentioning
confidence: 99%
“…Cooperative spontaneous emission processes have also been investigated in molecular solids, such as molecular aggregates and crystals, including Jaggregates [96,97], LH-2 photosynthetic antenna complexes [98], π-conjugated polymer thin films [99,100], H-aggregates [101,102], and tetracene thin films and nanoaggregates [103]. In all these studies, accelerated radiative decay was observed and attributed to cooperative emission, although SF, in the form observed in atomic systems (Section II) and molecular centers in crystals (Section III A), has not been reported and some of the reported results and claims remain controversial.…”
Section: B Molecular Aggregates and Crystalsmentioning
confidence: 99%
“…Such molecules pack in a herringbone arrangement with at least 2 molecules in a unit cell. [20][21][22][23] Here, the lower Davydov component ͑alias J-band͒ is weakly allowed along the crystal b direction, 20,[24][25][26] leading to b-polarized superradiant 0-0 emission 27 which diminishes with increasing disorder. [28][29][30][31] In helical MOPVn aggregates, coherence affects the PL spectrum in a manner similar to the ideal linear H-aggregates described above.…”
Section: Introductionmentioning
confidence: 99%